2008
DOI: 10.1007/s11274-008-9708-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Vibrio parahaemolyticus from seafoods along the southwest coast of India

Abstract: The work was aimed to study the microbial quality of the seafood sold in the domestic markets and incidence of Vibrio parahaemolyticus. Samples comprising of shellfish, finfish, and cephalopods were collected from various fish markets in and around Cochin. Presumed V. parahaemolyticus were identified by standard biochemical tests, and further confirmed by polymerase chain reaction targeting species-specific tl gene (450 bp). About 81% of the samples were found to exceed the limits specified for total plate cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…In a study on seafood products in China (Chao et al 2009), the incidence of this bacterium was found to be 56.6%. The rates of V. parahaemolyticus contamination of seafood by Chakraborty et al (2008) in India and by Costa Sobrinho et al (2011) in Brazil were reported as 64% and 100%, respectively. However, the incidence (28%) of V. parahaemolyticus in retail seafood reported here was relatively higher than that reported by Baffone et al (2000) (2011) suggested that 140 out of 239 shrimp samples from Chinese seafood markets were contaminated with V. vulnificus.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on seafood products in China (Chao et al 2009), the incidence of this bacterium was found to be 56.6%. The rates of V. parahaemolyticus contamination of seafood by Chakraborty et al (2008) in India and by Costa Sobrinho et al (2011) in Brazil were reported as 64% and 100%, respectively. However, the incidence (28%) of V. parahaemolyticus in retail seafood reported here was relatively higher than that reported by Baffone et al (2000) (2011) suggested that 140 out of 239 shrimp samples from Chinese seafood markets were contaminated with V. vulnificus.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ampicillin should be of great concern, because the drug represents the region's main treatment against infectious diarrhea in small children (Mandomando et al ., ). Our results regarding the antibiotic susceptibility of V. parahaemolyticus from India support those of previous studies, which show antibiotic resistance to have spread among environmental strains of the bacterium (Bhattacharya et al ., ; Chakraborty et al ., ). However, the present study is the first, to our knowledge, to report on the susceptibility of vibrios isolated from Swedish environments.…”
Section: Discussionmentioning
confidence: 97%
“…This was surprising as V. parahaemolyticus is known to be prevalent in Asia (2,5,6,7,8,9) and has been reported in Malaysia (12), which has similar environmental and other conditions that foster the proliferation of V. parahaemolyticus to that of Brunei. Moreover, a number of the samples were possibly imported into Brunei from Malaysia.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…3 It is therefore a leading cause of seafood-borne gastroenteritis, especially in countries where seafood consumption is high 4 as well as being responsible for foodborne disease outbreaks, with fatalities in Japan in 1950, 5,6 India, 2,7 China, 6,8,9 Taiwan, 10 Korea 11 and Malaysia. 12 The mechanism by which V. parahaemolyticus infects humans has yet to be entirely determined.…”
Section: Asian Journal Of Medical Sciences 5(2014) 33-39mentioning
confidence: 99%